Perlakuan Akuntansi Pajak Pertambahan Nilai pada PT. Tiran Makassar - SALIDA, AMRIZAL; Nawir, Imran (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2021)
This research aims to determine the suitability of value-added tax accounting actors at PT. Tiran Makassar with accounting treatment according to the VAT Law Number 42 of 2009, this type of research uses quantitative and qualitative data using comparative hypothesis and descriptive methods. Sources of data in this study are primary data consisting of interviews with PT. Tiran Makassar and secondary data in the form of documents from the company, namely, purchasing and sales data, profile, history, and company structure. This study focuses on value-added tax which focuses on purchasing and sales data of PT. Tiran Makassar, The results showed that the comparison of value-added tax accounting treatment at PT. Tiran Makassar and according to the Taxation Law Number 42 of 2009 concerning VAT have not complied with the applicable laws and regulations, where PT. Tiran Makassar in the acquisition of taxable goods (BKP) or taxable services (JKP) whose input tax is collected by the issuance of tax assessments. PT. Tiran Makassar only pays value-added tax (VAT) payable on the acquisition or utilization of taxable goods or taxable services after the issuance of a tax assessment.